The remarried empress. 1 - Alphatart (Novelist); Herelee (Remarried empress, 2022)
"Navier Ellie Trovi was the lifelong companion of Sovieshu, the emperor of the Eastern Empire, with whom she spent her youth discussing the empire they would build together. She was intelligent, compassionate, and courageous. She was the perfect empress of the Eastern Empire, until the day Sovieshu fell for another woman, demanding a divorce. However, it was Navier who shocked Sovieshu, his beloved mistress, and a speechless court as she coldly declared: "I accept this divorce ... and request an approval of my remarriage!" --